Characterizing cognitive aging of spatial and contextual memory in animal models - Foster, Thomas C.; DeFazio, R. A.; Bizon, Jennifer L. (Frontiers in Aging Neuroscience, 2012)
Episodic memory, especially memory for contextual or spatial information, is particularly vulnerable to age-related decline in humans and animal models of aging. The continuing improvement of virtual environment technology for testing humans signifies that widely used procedures employed in the animal literature for examining spatial memory could be developed for examining age-related cognitive decline in humans. The current review examines cross species considerations for implementing these tasks and translating findings across different levels of analysis. The specificity of brain systems as well as gaps in linking human and animal laboratory models is discussed.